(untitled) (Praxis Educativa, 2022)
Within the framework of the University of Mendoza’s extension project "Accompanying educational trajectories: the educational link between work teams", this article reviews and creates a synthesis of the theoretical tour done by the extension team, looking for delving into the main axes that emerged during the exchange of experiences and discussions about complexity, teamwork, interdiscipline, and educational link. In addition, the ideas related to construction of wisdom during the context of the pandemic are pointed out, and some experiences related to the institutions where we worked are highlighted. Our all-together reflection remarks the necessity of sustaining the accompaniment of educational processes under the condition of the pandemic in renewed and complex ways.